ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DI KABUPATEN KUTAI BARAT - Karun, Leonardo Dakori; Mintarti, Sri; Juliansyah, . (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2012)
The research was based on the reason for analyzing the factors that affect the economic growth that occurred in the West Kutai Regency. By using independent variables such as government expenditure, domestic investment, foreign investment and the amount of manpower, and also to testing and analyzing the influence of each independent variable on the dependent variable of economic growth.The analysis tools are quantitative analysis using multiple linear regression analysis with SPSS. Multiple linear regression analysis is used to determine how much influence government expenditure (X1), domestic investment (X2), foreign investment (X3), and the amount of manpower (X4) to The economic growth(Y). Based on the analysis, the independent variables (government expenditure, domestic investment, foreign investment and amount of manpower jointly affect the economic growth in the West Kutai Regency, with constant values for the constants in the regression equation -1005.538 while the regression coefficient for government expenditure variable (X1) = 1.894; domestic investment (X2) = 0.627; foreign investment (X3) = 0.083; and amout of manpower (X4) = 32.142.